صورة المستعمر في الأدب الإفريقي - حيدرة, هاجيرة (مكتبة كلية الأدب العربي والفنون, 2023)
ان أهم ما يميز الخطاب الأدبي والفكري عامة المعاصر أو التقليدي نزعته الواضحة لمناهضة التمثلات الغربية وخطابها الاستعماري والسيادي باختلاف مستوياته.وتجلى هذا في أعمال الكثير من الأدباء المتشبعين بالروح الوطنية والمعتزين بهويتهم أمثال موريس سنغور في السنغال واتشينو اتشيبي و اميه سيزار ودافيد ديوب وأمثالهم كثر.فهم قدموا الملامح الحقيقية لصورة إفريقيا بعيون افريقية اي في نطاق صورة الأنا . وأزاحوا ما قدمته الأقلام الغربية والأوروبية خاصة أو الإفريقية التي ترتدي القناع الأوروبي عن همجية ووثنية الإفريقي وتخلفه . والاهم من ذلك كشف الستار عن الهدف الحقيقي الذي دخل من اجله المستعمر إلي القارة السمراء المتمثل في النهب والسلب والتسيد The most important characteristic of literary and intellectual discourse in general, contemporary or traditional, is its clear tendency to oppose Western representations and its colonial and sovereign discourse at different levels. This was evident in the works of many writers imbued with the national spirit and proud of their identity, such as Maurice Senghor in Senegal, Achino Achebe, Ameh Cesar, David Diop and many others like them. They presented The true features of the image of Africa with African eyes, i.e. within the scope of the ego image. And they removed what Western and European pens offered, especially African ones, that wear the European cloak on the barbarism, paganism, and backwardness of the African. More importantly, the unveiling of the real goal for which the colonizers entered the brown continent is represented by plundering, plundering and domination.
دراسة نماذج
Keywords: الخطاب الفكري و التقليدي،الخطاب الاستعماري،التمثلات الغربية ،صورة إفريقيا; intellectual and traditional discourse, colonial discourse, Western representations, the image of Africa